2019
DOI: 10.4067/s0717-95022019000100022
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Sphenoid Sinus Dimensions in Turkish Healthy Adult Subjects: An MRI Study

Abstract: The aim of this study was to identify sphenoid sinus dimensions; and distance between columella nasal and sphenoid sinus; and columella nasal and hypophysis in healthy adult subjects using magnetic resonance imaging (MRI) and to evaluate differences between genders and age groups. The MRI results of 300 healthy subjects (192 females; 108 males) aged 18-68 years were studied. The midsagittal and axial images were used for shape of the sphenoid sinus, and the distance measurements of its related adjacent structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Gibelli et al highlighted a high frequency of the sellar type (74%) in their study (Gibelli et al 2018b). However, the post-sellar type was found to be most frequent (74.0%) in the present sample, which was in accordance with earlier data from Öksüzler et al andKim et al 2013b (Öksüzler et al 2019). Besides, present findings also revealed that a mature sinus (> 12 years) (Pallanch et al 2013) might exhibit postsellar extension until middle age.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Gibelli et al highlighted a high frequency of the sellar type (74%) in their study (Gibelli et al 2018b). However, the post-sellar type was found to be most frequent (74.0%) in the present sample, which was in accordance with earlier data from Öksüzler et al andKim et al 2013b (Öksüzler et al 2019). Besides, present findings also revealed that a mature sinus (> 12 years) (Pallanch et al 2013) might exhibit postsellar extension until middle age.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, the normal volume and mean maximum diameter recorded were 6576.92 mm 3 and 30.48 mm, respectively which was in accordance with the findings of Oliveira et al (Oliveira et al 2017). These values were somewhat smaller as compared to the dimensions reported in previous studies (Gibelli et al 2018a;Öksüzler et al 2019;Ozer et al 2018). A reasonable explanation for such contrasting results could be the existence of an ethnic variability, since the aforementioned authors (Gibelli et al 2018a;Öksüzler et al 2019;Ozer et al 2018) conducted their studies in Italian and Turkish subjects.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation